PLD1 and PLD2 differentially regulate the balance of macrophage polarization in inflammation and tissue injury. Issue 7 (23rd December 2020) - Hwang, Won Chan; Seo, Seol Hwa; Kang, Minju; Kang, Rae Hee; Di Paolo, Gilbert; Choi, Kang‐Yell; Min, Do Sik
Abstract: Phospholipase D (PLD) isoforms PLD1 and PLD2 serve as the primary nodes where diverse signaling pathways converge. However, their isoform‐specific functions remain unclear. We showed that PLD1 and PLD2 selectively couple to toll‐like receptor 4 (TLR4) and interleukin 4 receptor (IL‐4R) and differentially regulate macrophage polarization of M1 and M2 via the LPS–MyD88 axis and the IL‐4–JAK3 signaling, respectively. Lipopolysaccharide (LPS) enhanced TLR4 or MyD88 interaction with PLD1; IL‐4 induced IL‐4R or JAK3 association with PLD2, indicating isozyme‐specific signaling events. PLD1 and PLD2 are indispensable for M1 polarization and M2 polarization, respectively. Genetic and pharmacological targeting of PLD1 conferred protection against LPS‐induced sepsis, cardiotoxin‐induced muscle injury, and skin injury by promoting the shift toward M2; PLD2 ablation intensified disease severity by promoting the shift toward M1. Enhanced Foxp3 + regulatory T cell recruitment also influenced the anti‐inflammatory phenotype of Pld1 LyzCre macrophages. We reveal a previously uncharacterized role of PLD isoforms in macrophage polarization, signifying potential pharmacological interventions for macrophage modulation. Abstract : LPS and IL‐4 selectively activate PLD1 and PLD2 via TLR4 and IL‐4R, respectively. PLD isozyme‐specific function is mediated by LPS‐ and IL‐4‐triggered signaling via the MyD88 and JAK3 axis, followed by differential control of M1 and M2 macrophage polarization. PLD1 and PLD2 are indispensable for the polarization of M1 and M2, respectively, and reciprocally regulate macrophage polarization.